Análisis sobre la influencia que tiene la gestión de las mujeres en la Administración Bancaria, en Quito año 2014-2016 - Armendáriz Haro, Daniela Yadira (2017)
In the present article, a study was carried out on the impact of the management of women in banking administration; during the last years the presence of the same in different positions of executive prestige such as managers and managers has been evidenced. Many factors have contributed to the fact that they may be able to occupy stellar seats within banking institutions, as manifested in the report of the principles for the empowerment of women called equality is a good business, recommended by the organization of United nations, year 2015, however there are general activities hospital, hotel, commercial among others, where the role of women management is preponderant. A series of aspects have been analyzed in order to be able to determine which were the most influential in the course of their work. From this analysis it was possible to determine if his academic formation was determinant to be taken into account to occupy that position. It also shows the reasons that have prevented or delayed their promotion within the institution. Interviews and surveys were conducted with managers of different banks in the city of Quito, in order to know if gender barriers are limiting factors that prevented their professional growth, which enriched this study and allowed to recognize that the woman did not need to resemble her Behavior to that of a man